ByzRev 02.2020.031: Alessandro Garcea – Michela Rosellini – Luigi Silvano (eds.), Latin in Byzantium I, Late Antiquity and Beyond: (Corpus Christianorum, Lingua patrum 12). Turnhout: Brepols 2019. - Bara, Péter (The Byzantine Review, 2020)
Alessandro Garcea – Michela Rosellini – Luigi Silvano (eds.), Latin in Byzantium I, Late Antiquity and Beyond (Corpus Christianorum, Lingua patrum 12). Turnhout: Brepols 2019. 564 pp. – ISBN: 978-2-503-58492-8 (€ 230.00).